If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 18 + -15x = 10x + -60 Reorder the terms: 18 + 2x + -15x = 10x + -60 Combine like terms: 2x + -15x = -13x 18 + -13x = 10x + -60 Reorder the terms: 18 + -13x = -60 + 10x Solving 18 + -13x = -60 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 18 + -13x + -10x = -60 + 10x + -10x Combine like terms: -13x + -10x = -23x 18 + -23x = -60 + 10x + -10x Combine like terms: 10x + -10x = 0 18 + -23x = -60 + 0 18 + -23x = -60 Add '-18' to each side of the equation. 18 + -18 + -23x = -60 + -18 Combine like terms: 18 + -18 = 0 0 + -23x = -60 + -18 -23x = -60 + -18 Combine like terms: -60 + -18 = -78 -23x = -78 Divide each side by '-23'. x = 3.391304348 Simplifying x = 3.391304348
| 2(3x+1)+4(x-1)=3 | | 7(m-12)=15m | | x-0.6x-11=21 | | -(-10p+4r)= | | -5z+11=53-12z | | 7a-a=-48 | | 4x+6=18-2x | | 7(x+4)=105 | | 5(2x-1)=35 | | -4a=-40+6a | | -8x-4=-12 | | (-8)(2-9c)= | | 2x-15x-10x=-42 | | 13a+7a+18a= | | -4s+11-8s=35 | | 4=x+3(x) | | 4+5(s-2t)= | | 4=x+3*x | | 7x=70 | | 2(x-2)=1.4 | | 9(a+6)=113.4 | | 3x+1=-(x-9) | | 4(x-7)=0 | | 9p+5=14+8p | | 2(a+9)=22 | | x-3=25 | | -b+14=16 | | 176=8*14x | | 2t+4-3= | | 4(2x-1)+(4x+3)=0 | | 176=8*x | | p-20=-25 |